Territories innovating to monitor and assess progress towards sustainability - Project TerraCert; CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The TerraCert Project is developing an innovative approach to achieve sustainability in the Amazon region through the certification of territories. The project embraces four key dimensions: Agricultural transition with eco-efficiency in the Amazon The territories in the Amazon, mainly those in the deforestation arc, need to initiate and consolidate a transition from extensive and extractive production systems to others that value better the available natural resources by achieving higher eco-efficiency and productivity. This transition has to take place at the territorial level since it depends on interactions among rural landholdings, public agencies and private organizations, markets and socio-technical innovation networks. Landscape and territorial management Solutions to reconcile production and conservation Sustainable territorial management requires reconciling production and conservation goals. The territory constitutes a privileged level, comprising both spatial and eco-systemic dimensions, where achieving those commitments is possible. Assessing the trajectory of progress towards more sustainable territorial management should be the target of landscape monitoring and planning. Public–private institutional arrangements to promote agricultural transition with eco-efficiency Public and private actors’ involvement in producing a consensual pact is a crucial factor for building a project of sustainable territorial development, which could support a process of territorial certification. The ongoing decentralization process, which grants greater responsibilities to municipal governments in the Amazon, constitutes an opportunity for local actors to achieve greater autonomy in decision-making processes leading to improved management of their territories. Territorial certification Highlighting and monitoring progressive sustainability efforts A certification system, designed in a participatory way, can help to monitor and verify the progressive evolution of territories towards sustainability. It can increase the visibility of the territories that, through the engagement of local actors, make efforts to improve the social, economic and environmental performance of their territories, thus improving their attractiveness to investors and State agencies when targeting public policies. Improving the attractiveness of territories and lowering territorial risk also generates indirect bene ts such as local employment generation, increases in the value of land and a positive image for local businesses.